Adherence to anticoagulant treatment with dabigatran in a real‐world setting. Issue 7 (15th July 2013) - Schulman, S.; Shortt, B.; Robinson, M.; Eikelboom, J. W.
Summary: Background: In clinical trials, adherence to a prescribed regimen with dabigatran was enhanced by frequent follow‐up visits and pill counts. Objectives: To describe the experience of dabigatran treatment in clinical practice, focusing on adherence. Patients/methods: In a cross‐sectional cohort study, we interviewed 103 patients treated for at least 3 months with dabigatran and followed by our anticoagulant clinic. We obtained information on the number of capsules of dabigatran dispensed by the pharmacy of each patient covering the entire treatment period and calculated the adherence. In addition, information on the frequency of missed capsules, bleeding, thromboembolic events and other adverse events, specifically dyspepsia, was captured from the interviews and medical records. Results: The mean age was 75.5 (± 8.5) years, 46% were females, and the mean CHADS2 score was 2.5. Dispensation data were obtained for 99 patients and adherence was 99.7% (median; interquartile range 94.6%–100%) with 11 patients showing < 80% adherence. During their interview, 31 patients (30%) acknowledged that they sometimes had missed taking the medication, ranging from 'twice in 6 years' to 'every day'. One additional patient with adherence < 80% was identified. Twenty‐one patients (20%) reported bleeding complications, two of which were major; one patient had an ischemic stroke and 34 (33%) reported some degree of dyspepsia. There were no significant differences in the results between RE‐LY study‐experienced and study‐naïve patients. Conclusion: In our clinical practice adherence to the twice‐daily dabigatran regimen was generally good, although 12% of the patients had an inadequate adherence. Routine feedback from the pharmacies could inform the physician to improve the anticoagulant management.